Mechanical stimuli-induced CCL2 restores adult mouse cells to regenerate hair follicles - Wang Wu; Wei Zhou; Jingwei Jiang; Mengyue Wang; Jinwei Zhang; Jing Yang; Qu Tang; Huawen Liu; Deming Liu; Wei Xu; Julia Li Zhong; Li Yang; et al. (Elsevier, 2023)
Aged cells have declined regenerative ability when subjected to environmental insult. Here we elucidate the mechanism by which mechanical stimulus induces hair regeneration at the microenvironmental regulation level using the hair plucking and organoid culture models. We observed that the skin cells harvested from post-plucking day 3 (PPD3) have the best self-organizing ability during skin organoid culture and have the highest hair regeneration upon transplantation. By bulk RNA sequencing (RNA-seq) and single-cell RNA-seq analysis and in situ hybridization, we identified that the chemokine signaling pathway genes including CCL2 are significantly increased in the skin at PPD3 and in skin organoid cultures. Immunostaining shows that the PPD3 skin epithelial cells have increased multipotency, which is verified by the ability to self-organize to form epidermal aggregates during organoid culture. By adding CCL2 recombinant protein to the organoid culture using an environmental reprogramming protocol, we observed the PPD0 adult skin cells, which lose their regenerative ability can self-organize in organoid culture and regenerate hair follicles robustly upon transplantation. Our study demonstrates that CCL2 functions in immune regulation of hair regeneration under mechanical stimulus, and enhances cell multipotency during organoid culture. This provides a therapeutic potential for future clinical application.